The space between us - Martinez, Jessica (New York : Simon Pulse, 2013)
Seventeen-year-old Amelia feels like her life might be getting back on track after a bad break-up when her younger sister's pregnancy gets them both banished to Canada, where new relationships are forged, giving Amelia a new perspective.
Keywords: Sisters -- Fiction; Pregnancy -- Fiction